Gestión y planificación de destinos en municipalidades provinciales - Cayo, Noemí; Flores, Antonio; Apaza-Tarqui, Alejandro (Instituto Universitario de Innovación Ciencia y Tecnología Inudi Perú, 2022)
This book is an adaptation of a research presented to the National University of the Altiplano whose purpose was to evaluate the level of tourism planning and its correlation with the management of destinations of the Provincial Municipality in the destination Puno province (Lake Titicaca, Peru), For this purpose, a quantitative approach methodology was chosen, with a descriptive and correlational level design, non-experimental, cross-sectional, seeking to determine the degree of correlation between the variables. From a non-probabilistic sampling of an intentional type, applied to the managers and stakeholders of the destination. The results allowed us to conclude that tourism planning is regular in its compliance, since 55.17% of the total sample evaluates consider that the objectives were not achieved for the most part. In addition, with the Chi Square test it was determined that there is a correlation between compliance with tourism planning and destination management in the province of Puno (Peru).